2009
DOI: 10.1111/j.1365-2486.2009.01952.x
|View full text |Cite
|
Sign up to set email alerts
|

Strong links between teleconnections and ecosystem exchange found at a Pacific Northwest old‐growth forest from flux tower and MODIS EVI data

Abstract: Variability in three Pacific teleconnection patterns are examined to see if net carbon exchange at a low-elevation, old-growth forest is affected by climatic changes associated with these periodicities. Examined are the Pacific Decadal Oscillation (PDO), Pacific/ North American Oscillation (PNA) and El Niñ o-Southern Oscillation (ENSO). We use 9 years of eddy covariance CO 2 , H 2 O and energy fluxes measured at the Wind River AmeriFlux site, Washington, USA and 8 years of tower-pixel remote sensing data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 84 publications
(119 reference statements)
1
11
0
Order By: Relevance
“…In addition, we should be aware that long‐term land carbon fluxes simulated by state‐of‐the‐art DGVMs still have notable uncertainties due to parameterization and structure deficiencies in the ecosystem models, even if the ensemble of nine individual ecosystem models allows characterization of model spread. The development of flux tower measuring carbon fluxes allows us to bring independent data‐driven CO 2 flux estimates to study the relationships between teleconnections and carbon fluxes and compare them with those obtained from ecosystem models [ Desai et al ., ; Wharton et al ., ]. We thus calculated global and regional correlations between teleconnections and CO 2 fluxes based on the extrapolation of flux tower measurements using machine‐learning algorithms from the FLUXCOM project for the period 1982–2012 [ Jung et al ., ] and compared them to that of the TRENDY modelled fluxes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we should be aware that long‐term land carbon fluxes simulated by state‐of‐the‐art DGVMs still have notable uncertainties due to parameterization and structure deficiencies in the ecosystem models, even if the ensemble of nine individual ecosystem models allows characterization of model spread. The development of flux tower measuring carbon fluxes allows us to bring independent data‐driven CO 2 flux estimates to study the relationships between teleconnections and carbon fluxes and compare them with those obtained from ecosystem models [ Desai et al ., ; Wharton et al ., ]. We thus calculated global and regional correlations between teleconnections and CO 2 fluxes based on the extrapolation of flux tower measurements using machine‐learning algorithms from the FLUXCOM project for the period 1982–2012 [ Jung et al ., ] and compared them to that of the TRENDY modelled fluxes.…”
Section: Resultsmentioning
confidence: 99%
“…Several reasons may be responsible for the differences. The large-scale circulation patterns have different effects on climate at the three sites due to their different geographic location (Table 1), and CO 2 exchange responds differentially with respect to latitude and climatic variations [e.g., Nemani et al, 2003;Gong and Ho, 2003;Notaro et al, 2006a;Hember and Lafleur, 2008;Grant et al, 2009;Wharton et al, 2009]. Another possible reason is that the three AmeriFlux research sites have different forest composition species, which affects the response of CO 2 exchange to the climate [e.g., Hadley et al, 2009;Richardson et al, 2009].…”
Section: Application Of the Methodology To Other Sitesmentioning
confidence: 99%
“…[4] Large-scale circulation patterns influence the location and intensity of synoptic atmospheric pressure systems, and thereby significantly modify northern midlatitude climate [e.g., Wallace and Gutzler, 1981;Barnston and Livezey, 1987;Hurrell, 1995Hurrell, , 1996 and ecosystems [e.g., Goldstein et al, 2000;Freedman et al, 2001;Morgenstern et al, 2004;Urbanski et al, 2007;Hember and Lafleur, 2008;Grant et al, 2009;Wharton et al, 2009]. Over the northeast United States, previous studies have demonstrated that the climate and circulation features are strongly influenced by large-scale circulation patterns in the Pacific, Atlantic and Arctic regions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the effect of the phase of the El Niño‐Southern Oscillation (ENSO) on global‐scale photosynthesis and respiration, with ramifications for the global atmospheric CO 2 growth rate, has been particularly well studied (e.g., Gloor et al, ; Schwalm et al, ). These oscillations are themselves related to regional variability in multiple meteorological factors that may have additive or interactive effects on ecosystem carbon exchange (e.g., Jones et al, ; Knorr et al, ; Potter et al, ; Wharton et al, ).…”
Section: Introductionmentioning
confidence: 99%